Global to small island; a cross-scale foresight scenario exercise. Issue 5 (9th September 2020) - Drakes, Crystal; Cashman, Adrian; Kemp-Benedict, Eric; Laing, Timothy
Abstract : Purpose: The use of socio-economic scenarios in small island developing states (SIDS) when assessing, and planning for, the impacts of global changes on national socioeconomic and environmental systems is still in its infancy. The research conducts a cross-scale foresight scenario exercise to produce regional scenarios and national storylines for Caribbean islands that are of "partial" consistency to the shared socioeconomic pathways (SSPs) and representative concentration pathways (RCPs) and shows how future socioeconomic and climatic changes can be applied to inform natural resource management decisions. Design/methodology/approach: To develop the scenarios, the study uses a three-staged linking process using mixed methods to "triangulate" each technique to compensate for weaknesses of one method by introducing a complementary method at each stage. A participatory-expert stepwise approach with feedback loops is used and complemented with a climate sensitive tourism water demand model. Findings: Four regional exploratory socio-economic scenarios were constructed that are partially consistent with global scenarios. In addition, national storylines for four island states were developed based on the regional scenarios. Using RCP 4.5 hotel water demand in Barbados is estimated under three of the regional scenarios based on compatibility. The results indicate there is a 17% difference between the highest and lowest estimated water demand, indicating the effect of varying socio-economic conditions on water demand. Originality/value: The paper contributes to the literature by presenting regional socio-economic scenarios, specifically for SIDS, that are partially consistent with both global climatic RCPs and SSPs using a cross-scale approach. The scenarios are then used to demonstrate how future socio-economic pathways impact on freshwater demand.